2018
DOI: 10.1016/j.jsams.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol consumption, masculinity, and alcohol-related violence and anti-social behaviour in sportspeople

Abstract: Alcohol-related aggression and anti-social behaviour appear to be problematic in UK university sportspeople, and is related to masculinity and excessive drinking. Interventions that reduce excessive alcohol consumption, masculine norms and associated within-sport violence, could be effective in reducing alcohol-related aggression and antisocial behaviour in UK sportspeople.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 28 publications
0
18
0
1
Order By: Relevance
“…Of these, three articles were from data collection efforts designed to measure HTO victimization among college students (Diep, Knibbe, Giang, & De Vries, 2015;Hallett et al, 2012;Langley, Kypri, & Stephenson, 2003). Of the 15 other studies, four included brief sections about HTO (i.e., Harvard's College Alcohol Survey, the Canadian Campus Survey, Ireland's College Lifestyle and Altitudinal Survey, and the Study to Prevent Alcohol-Related Consequences), two included brief sections about alcohol-related consequences in which a fewer than five HTO were included (Rinker, Young, Krieger, Lembo, & Neighbors, 2017;Strunin et al, 2014), and eight focused on a few specific HTO (Araas & Adams, 2008;Fair & Vanyur, 2011;Howard, Griffin, & Boekeloo, 2008;Neal & Fromme, 2007;O'Brien et al, 2017;Presley & Pimentel, 2006;Reed, Amaro, Matsumoto, & Kaysen, 2009;Wilhite, Mallard, & Fromme, 2018). As shown in Figure 2, this means most of the research studies on college HTO included fewer than five harms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, three articles were from data collection efforts designed to measure HTO victimization among college students (Diep, Knibbe, Giang, & De Vries, 2015;Hallett et al, 2012;Langley, Kypri, & Stephenson, 2003). Of the 15 other studies, four included brief sections about HTO (i.e., Harvard's College Alcohol Survey, the Canadian Campus Survey, Ireland's College Lifestyle and Altitudinal Survey, and the Study to Prevent Alcohol-Related Consequences), two included brief sections about alcohol-related consequences in which a fewer than five HTO were included (Rinker, Young, Krieger, Lembo, & Neighbors, 2017;Strunin et al, 2014), and eight focused on a few specific HTO (Araas & Adams, 2008;Fair & Vanyur, 2011;Howard, Griffin, & Boekeloo, 2008;Neal & Fromme, 2007;O'Brien et al, 2017;Presley & Pimentel, 2006;Reed, Amaro, Matsumoto, & Kaysen, 2009;Wilhite, Mallard, & Fromme, 2018). As shown in Figure 2, this means most of the research studies on college HTO included fewer than five harms.…”
Section: Resultsmentioning
confidence: 99%
“…The three devoted studies aimed to determine the prevalence and risk factors for HTO among college students (Diep et al, 2015;Hallett et al, 2012;Langley et al, 2003), and one study compared the distribution of HTO among drinkers and non-drinkers (Cabalatungan, 2015). Eleven articles investigated specific populations (e.g., sports fans, athletes), campus settings (e.g., total alcohol bans) or specific HTO (e.g., sexual assault or date fighting) (Fair & Vanyur, 2011;Harford, Wechsler, & Muthen, 2003;Howard et al, 2008;Martin et al, 2009;Neal & Fromme, 2007;O'Brien et al, 2017;Reed et al, 2009;Rhodes et al, 2009;Wechsler, Lee, Gledhill-Hoyt, & Nelson, 2001;Wilhite et al, 2018). Seven articles investigated associations between independent variables (e.g., drinking levels and protective behavioral strategies) and HTO (Abar, Mallett, Turrisi, & Abar, 2016;Araas & Adams, 2008;Cabalatungan & McCarthy, 2015;Nelson, Xuan, Lee, Weitzman, & Wechsler, 2009;Presley & Pimentel, 2006;Weitzman & Chen, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…Alcohol consumption is consistently associated with physical violence across studies ( O’Brien et al, 2017 ; Sabina et al, 2017 ; Schuurman et al, 2015 ), although the magnitude of alcohol consumption varies. This study reported a high proportion (57%) of men aged 15–34 years who consumed alcohol prior to receiving an injury from physical violence.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified one reason for a higher proportion of men engaging in alcohol drinking: that drinking could serve as a marker of masculinity or male camaraderie. [45][46][47] This may encourage male drinkers to deny or minimize problems resulting from their drinking or to regard drunken behavior as normal or permissible.…”
Section: Discussionmentioning
confidence: 99%